2021
DOI: 10.18632/aging.202834
|View full text |Cite
|
Sign up to set email alerts
|

A ketogenic diet impacts markers of mitochondrial mass in a tissue specific manner in aged mice

Abstract: Declines in mitochondrial mass are thought to be a hallmark of mammalian aging, and a ketogenic diet (KD) may prevent the age-related decreases in mitochondrial content. The objective of this study was to investigate the impact of a KD on markers of mitochondrial mass. Mice were fed an isocaloric control diet (CD) or KD from 12 months of age. Tissues were collected after 1 month and 14 months of intervention, and a panel of commonly used markers of mitochondrial mass (mitochondrial enzyme activities and levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 53 publications
(35 reference statements)
2
16
0
Order By: Relevance
“…Recently, it was reported that long-term exposure to a ketogenic diet attenuated the aging-related decline of relative muscle mass [ 173 ] and increased markers of mitochondrial content in aged skeletal muscles [ 174 ]. Interestingly, the ketone body β-hydroxybutyrate, which is elevated during nutritional ketosis, was shown to induce mitophagy in young and aged myocytes [ 175 ] and elicits favorable mitochondrial adaptations in myocytes [ 176 ].…”
Section: Enhancing Mitophagy To Counteract Sarcopenia: Potential Applicability and Future Researchmentioning
confidence: 99%
“…Recently, it was reported that long-term exposure to a ketogenic diet attenuated the aging-related decline of relative muscle mass [ 173 ] and increased markers of mitochondrial content in aged skeletal muscles [ 174 ]. Interestingly, the ketone body β-hydroxybutyrate, which is elevated during nutritional ketosis, was shown to induce mitophagy in young and aged myocytes [ 175 ] and elicits favorable mitochondrial adaptations in myocytes [ 176 ].…”
Section: Enhancing Mitophagy To Counteract Sarcopenia: Potential Applicability and Future Researchmentioning
confidence: 99%
“…The increase in red gastrocnemius muscle mitochondrial mass may contribute to the previous observation that aged mice on a KD perform better in muscle strength and endurance tests than CD animals [21]. However, these changes in mitochondrial mass were not reflected in the hindlimb skeletal muscle mitochondrial markers assayed at this same length of time on diet in our previous study [10]. This could indicate the markers used were not sensitive enough to pick up the differences in muscle tissues.…”
Section: Discussionmentioning
confidence: 68%
“…In our previous skeletal muscle work [ 10 ], mitochondrial markers were analyzed in homogenates of the entire hindlimb skeletal muscle, and it was not possible to determine the response of specific muscles to a KD. To directly address this issue, we harvested the red gastrocnemius muscle to measure mitochondrial content with TEM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations